2006
DOI: 10.1515/jpem.2006.19.1.65
|View full text |Cite
|
Sign up to set email alerts
|

A Daily Comprehensive Muscle Training Programme Increases Lean Mass and Spontaneous Activity in Children with Prader-Willi Syndrome after 6 Months

Abstract: The reduction of spontaneous physical activity (PA) and of muscle tissue are thought to be major causes of fat accretion and metabolic deterioration in Prader-Labhart-Willi syndrome (PWS). We investigated whether a generalized physical training programme in a home setting improves these parameters. The prospective study included 11 prepubertal children (mean age 8.7 years, range 5.9-11.8) with documented PWS and under contir"jus growth hormone treatment for at least 2.8 years. Seven children were enrolled in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 15 publications
3
66
0
Order By: Relevance
“…In children who have PWS, a complex genetic disorder causing a profound aversion to PA, we were able to show that the introduction of a 10-minute daily strength training led to a significant increase of spontaneous PA, with the daily walking distance improving from an average 3.7 to 5.8 km. 8 In 12-to 13-year-old ice hockey-playing boys we found that 16 weeks of strength training not only increases leg and arm strength, but also significantly increases spontaneous PA outside of training. 9 The main objective of this randomized controlled intervention study was to assess whether participation in a school-based strength training program 2 hours per week would increase spontaneous daily PA outside of training in normal schoolchildren.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In children who have PWS, a complex genetic disorder causing a profound aversion to PA, we were able to show that the introduction of a 10-minute daily strength training led to a significant increase of spontaneous PA, with the daily walking distance improving from an average 3.7 to 5.8 km. 8 In 12-to 13-year-old ice hockey-playing boys we found that 16 weeks of strength training not only increases leg and arm strength, but also significantly increases spontaneous PA outside of training. 9 The main objective of this randomized controlled intervention study was to assess whether participation in a school-based strength training program 2 hours per week would increase spontaneous daily PA outside of training in normal schoolchildren.…”
Section: Discussionmentioning
confidence: 76%
“…They have very low PA and increased their spontaneous PA in response to a strength-training intervention by 57%. 8 In prepubertal children, less specific types of strength-training interventions are also able to increase PA. Sigmund et al showed that 45 minutes more PE including highintensity activities such as jumps, hops, and sprints also increases leisure time PA. 23 The mechanism by which strength training induces spontaneous PA remains unclear. There may be an endocrine signaling coming from the musculoskeletal system, which is responsible for a positive feedback between physical strength and PA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily muscle training increases physical activity and lean body mass. 152 Psychosis is reported to respond well to selective serotonin reuptake inhibitors but not to mood stabilizers. 150 A group home for individuals with PWS that incorporates regulation of behavior and weight and ensures adequate physical activity may prevent morbid obesity (personal observation).…”
Section: Childhoodmentioning
confidence: 99%
“…Previous studies have shown that significant differences have been reported in LBM between athletes and nonathletes (35), changes following exercise (14 -16), and longitudinal studies or exercise training studies of special populations (e.g., cystic fibrosis, Prader-Willi syndrome, etc.) (28,42,44,50). However, few studies have examined the influence of free-living, habitual PA on LBM accrual during adolescence, a critical period of growth affecting body composition and those that have, for the most part, been cross-sectional in design and thus unable to tease out the independent effects of PA from those of growth and maturation (12,21,25).…”
mentioning
confidence: 99%